2014
DOI: 10.1186/1471-2164-15-596
|View full text |Cite
|
Sign up to set email alerts
|

An integrated genomic and metabolomic framework for cell wall biology in rice

Abstract: BackgroundPlant cell walls are complex structures that full-fill many diverse functions during plant growth and development. It is therefore not surprising that thousands of gene products are involved in cell wall synthesis and maintenance. However, functional association for the majority of these gene products remains obscure. One useful approach to infer biological associations is via transcriptional coordination, or co-expression of genes. This approach has proved useful for several biological processes. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 92 publications
4
27
0
3
Order By: Relevance
“…Although silica is a reported plant cell wall component [22][23][24]48], little is known about its effects on cell wall networks. Systems biology analysis based on correlations of large sample populations is a powerful approach to address these issues [44,45]. In this study, we have observed a significant positive correlation between silica and three major wall polymers (cellulose, hemicelluloses and lignin) using 42 distinct cell wall mutants.…”
Section: Discussionmentioning
confidence: 87%
“…Although silica is a reported plant cell wall component [22][23][24]48], little is known about its effects on cell wall networks. Systems biology analysis based on correlations of large sample populations is a powerful approach to address these issues [44,45]. In this study, we have observed a significant positive correlation between silica and three major wall polymers (cellulose, hemicelluloses and lignin) using 42 distinct cell wall mutants.…”
Section: Discussionmentioning
confidence: 87%
“…Both AtMYB15 and AtMYB38 interact with a harpin protein to modulate the plant’s tolerance to infestation by the green peach aphid [16]. The phylogenetic analysis indicated that CmMYB19 was included in the group of lignin biosynthesis or wall deposition [11], of which AtMYB103 , AtMYB61 , AtMYB55 [17] AtMYB83 , AtMYB46 [18], AtMYB86 [19], AtMYB26 [20], and AtMYB50 [21] have been proved to be involved in the biosynthesis of lignin; however, the roles of AtMYB18 , AtMYB 19, AtMYB 45 and AtMYB 67 in lignin biosynthesis have not been described yet. Here, CmMYB19 overexpression enhanced the accumulation of lignin.…”
Section: Discussionmentioning
confidence: 99%
“…KORRIGAN protein, a GH 9 A family member, can play a role in cellulose biosynthesis by either cleaving a sterol-cellodextrin substrate or removing glucan chains incorrectly assembled in the growing microfibrils. KORRIGAN (kor) mutants show reduced cellulose levels and imperfect plant growth, while overexpression of PtCel 9 A 1 (GH 9 A) leads to reduced cellulose CrI and increased biomass yield [83]. In rice mutants, the expression levels of OsGH 9 B family genes are meaningfully associated with cellulase activity and cellulose CrI, recommending that GH9B family should play a role in cellulose degradation.…”
Section: Cellulose Biosynthesis and Degradationmentioning
confidence: 99%
“…In rice mutants, the expression levels of OsGH 9 B family genes are meaningfully associated with cellulase activity and cellulose CrI, recommending that GH9B family should play a role in cellulose degradation. It have reported that the overexpression of PtGH 9 B 5 /C 2 genes redound to low plant growth and biomass yield, but RNAi silencing of the AtGH 9 C 2 gene could reduce cellulose CrI and improve biomass yield [83].…”
Section: Cellulose Biosynthesis and Degradationmentioning
confidence: 99%